2022
DOI: 10.1101/2022.12.15.22283478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and Multi-omic Risk Assessment of Alzheimer’s Disease Implicates Core Associated Biological Domains

Abstract: Alzheimer's disease (AD) is the predominant dementia globally, with heterogeneous presentation and penetrance of clinical symptoms, variable presence of mixed pathologies, potential disease subtypes, and numerous associated endophenotypes. Beyond the difficulty of designing treatments that address the core pathological characteristics of the disease, therapeutic development is challenged by the uncertainty of which endophenotypic areas and specific targets implicated by those endophenotypes to prioritize for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 135 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…The potential impact of studies in this pathway is supported by high TREAT-AD scores ( Fig. 2 ) for many of the genes in this pathway 82…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The potential impact of studies in this pathway is supported by high TREAT-AD scores ( Fig. 2 ) for many of the genes in this pathway 82…”
Section: Resultsmentioning
confidence: 96%
“…The common regulation of these genes in microglia across aging and AD and in mouse and man provides a compelling result and to determine if these genes may warrant further mechanistic study, TREAT-AD scores 82 were collected for each of these genes and compared to the distribution of all annotated genes ( Figure 12 ). The TREAT-AD score was developed as part of NIH consortia to prioritize AD targets for investigation and potentially therapeutic targets.…”
Section: Resultsmentioning
confidence: 99%
“…One method to address how altered regulation of specific genes impacts disease etiology is to capture the gene in the context of the larger biological process. We have designed biological domains (or endophenotypes) of AD that are constructed from extensive Gene Ontology (GO) term collection, leveraging the gene to GO‐term annotation relationships, to place that gene in a broader biological context 47 . The up‐ and downregulated genes within any one biological domain can be used to “heat‐map” the subordinate processes relative to the disease state.…”
Section: Harnessing Resilience To Target Cognitive Declinementioning
confidence: 99%
“…If targets are judged to not be tractable, the starting gene lists are expanded to incorporate other genes that are in the same network (using co-expression or pathway annotation information). 16 In addition to selection of individual understudied targets, we are developing resources to interrogate a set of functionally connected targets, by developing TEPS for multiple targets within one specific protein module. Deep proteomic profiling study of AD and control brains from AMP-AD revealed new AD-related protein coexpression modules that were highly preserved across cohorts and brain regions.…”
Section: Tep Targets From Ad Systems Biologymentioning
confidence: 99%
“…Following this initial scoring, targets are evaluated for therapeutic potential, with an emphasis on tractability. If targets are judged to not be tractable, the starting gene lists are expanded to incorporate other genes that are in the same network (using co‐expression or pathway annotation information) 16 …”
Section: Introductionmentioning
confidence: 99%